School emphasis on academic success: the role of principal qualifications - Sideridis, Georgios; Alghamdi, Mohammed (Frontiers in Psychology, 2024)
The purpose of the present study was to relate a principal's qualifications with a school's emphasis on academic success. Participants were n=206 principals of respective schools in Saudi Arabia that took part in the study as a function of the TIMSS-2019 assessment. Principals were administered the eleven-item "School Emphasis on Academic Success" scale. A binary covariate defining low and high principal qualifications was computed. The Multiple Indicators Multiple Causes (MIMIC) model was involved with the latent means of both a general and three specific factors being regressed on the covariate to evaluate latent mean differences across differentially qualified principals. Furthermore, each one of the instrument's indicators was regressed on the principal covariate to evaluate the presence of Differential Item Functioning (DIF) or in other words additional effects due to item content. Results indicated a significant omnibus effect for the general factor only, with highly qualified principals holding significantly more positive beliefs about how parents, teachers, and students feel about their school's emphasis attitudes toward their school's emphasis on academic success. Further analyses at the item level indicated that "teacher expectations" were the single item presenting a DIF effect with highly qualified principals having stronger beliefs about their teacher's expectations of student success over and above the latent factor mean. Results are discussed on how they inform educational policy and practice.